San Jose during the Japanese occupation. - Pefianco, Arthur A (1994.)
This study is about the political and economic conditions of San Jose and the socio-cultural activities in the town during the Japanese occupation., The objectives are: to trace the events that led to the occupation of San Jose; To know the living conditions and the means of livelihood of the people together with the trading and commercial activities; and, to present a picture of community life as well as the cultural activities and other forms of recreation and entertainment present during the Japanese occupation. Books, documents, published manuscripts, etc. that contain information regarding San Jose during the Japanese occupation were used. Also, oral history through one on one interviews was conducted. Informants are residents of San Jose as well as those who were present during the Japanese occupation. They are now retired public teachers, government employees, professional and military men, with some still engaged in business. (Please see about Informants) The study was able to bring into light the situation of San Jose during the Japanese occupation. The town was occupied by the Japanese with an armed resistance. The set-up of the municipal government of San Jose was basically the same as before, except that it was a puppet government. the economic activities were necessarily limited as farmers and fishermen were afraid to go out farming and fishing. There was a shortage of food and prices of commodities rose. The people coped up with the economic condition through livelihood projects and finding ways and means to substitute necessities that were lacking. Also, the Japanese provided employment in their military office and in their owned business. Socio-cultural activities were normal in the sense that the Japanese tolerated them as long as these did not threaten them. Generally, atrocities were not experienced by Sanjosenhons because its leaders negotiated with the Japanese to spare the capital town from abuses and cruelties9of the soldiers in return for civilian cooperation with them.
Thesis (Undergraduate, Bachelor of Arts in History) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Japanese Occupation -- San Jose